The Effect of Digital Promotion and Destination Attractiveness on the Cultural Commodification Process at the Garut Ram Tourism Site - Avrianto, Alam; Murwenie, Ira; Farisya, Ghaida (Universitas Insan Cendekia Mandiri, 2025)
This study aims to analyze the influence of digital promotion and destination attractiveness on the process of cultural commodification in the Domba Tourism destination in Garut Regency, Indonesia. The Garut ram fighting tourism, a unique local cultural heritage, has yet to gain competitive strength compared to other destinations due to limited promotion and a lack of appealing cultural presentation. This research uses a quantitative approach with a descriptive-verificative method. Data were collected through a closed questionnaire distributed to 460 respondents who had visited the Domba Tourism site and were active social media users. The results of the regression analysis show that both digital promotion and destination attractiveness significantly influence cultural commodification, with digital promotion having a more dominant effect. Digital promotion plays a crucial role in expanding the reach of local cultural information and transforming traditional practices into attractive tourism products for both domestic and international markets. The study recommends optimizing an integrated digital marketing strategy to enhance the competitiveness of cultural tourism and support the sustainable preservation of local culture.